Impact of regulatory changes on first- and second-generation antipsychotic drug consumption and expenditure in Italy. - Andretta, M; Ciuna, A; Corbari, L; Cipriani, A; Barbui, C (2005)
BACKGROUND: In 1994 a change in drug reimbursement status was implemented in Italy according to cost-effectiveness criteria. The aim of this study was to examine the impact of these changes on the use of antipsychotic (AP) drugs. METHODS: Data concerning actual quantities of antipsychotic agents dispensed in Italy from 1995 to June 2003 were obtained from the Italian Ministry of Health. For each antipsychotic agent, the number of defined daily doses (DDDs) per 1,000 inhabitants per day was calculated, as well as the annual expenditure in Euros. RESULTS: From 1995 to June 2003 prescriptions for first-generation antipsychotic agents (FGAs) progressively decreased from 2.54 to 2.0 DDD/1,000/day; in contrast, prescriptions for second-generation antipsychotic agents (SGAs) progressively rose up to 1.75 DDD/1,000/day in 2003. Overall, from 1995 to 2003 antipsychotic prescriptions rose from 2.54 to 3.75 DDD/1,000/day. In 2003 the antipsychotic drug most frequently used was haloperidol, followed by olanzapine and risperidone. In 2003 the use of SGAs accounted for nearly 50% of overall DDD/1,000/day of AP agents. The cost of these new drugs, however, accounted for more than 80% of the total AP expenditure. CONCLUSIONS: In Italy, the progressive increase in the utilisation of SGAs has been accompanied by a moderate decrease in the utilisation of phenothiazines and by an almost constant use of butyrophenones. The policy of reimbursing the use of SGAs only in subjects who could not tolerate FGAs eventually failed to significantly affect the pattern of antipsychotic consumption and expenditure; moreover, when this policy was eliminated at the beginning of 2001, the pattern of consumption and expenditure did not change.